Where Higher Power Handling Capability is Required - IGCT is the Right Choice - Thomas Stiasny; Vasileios Kappatos; Thomas Setz; Sven Klaka; Makan Chen; Madhan Mohan (Kongzhi Yu Xinxi Jishu)
Integrated gate-commutated thyristor (IGCT) is described as ideal switch in high power applications, not only because of its high reliability, but also for its low device losses resulting in low system losses. IGCT is compared with state of the art IGBT, concerning losses on device level as well as on system level in a 3-level topology. Due to the thyristor characteristic as the basic nature of device, separate clamp circuit design is needed to allow for highly reliable operation of the switches together with their freewheeling diodes in a system. Also special considerations apply for fault cases. The important details for such circuit design and a fault current protection strategy are explained. IGCT is a device with significant potential to develop for higher power handling. Latest development results are presented.